Smoking is an important factor that affects peripheral blood progenitor cells yield in healthy male donors. Issue 1 (6th November 2019) - Zhen, Changqing; Fang, Xiaosheng; Ding, Mei; Wang, Xianghua; Yuan, Dai; Sui, Xiaohui; Liu, Xin; Zhang, Lingyan; Xu, Hongzhi; Li, Ying; Wang, Xin
Abstract: Background: Smoking could reduce the CD34+ cells in peripheral blood of healthy individual. This study aimed to investigate the correlation between smoking load and the effect of peripheral blood hematopoietic progenitor cells (PBPCs) mobilization by granulocyte colony‐stimulating factor (G‐CSF) alone in healthy donors. Methods: Retrospective analysis was performed on 145 healthy adult PBPCs donors who underwent PBPCs mobilization and collection. Smoking factors were evaluated and correlated with mobilization responses, as indicated by the collected CD34+ cells concentration. Results: The collected CD34+ cells concentration was closely related to pre‐CD34 ( P  < .001) and CD34+ cells collected per volume blood processed ( P  < .001) which suggested that collected CD34+ cells concentration was a reliable indicator of PBPCs mobilization efficiency. The heavy smoking donors revealed significantly lower collected CD34+ cells concentration, compared to that of the nonsmoking ( P  < .001) and light smoking donors ( P  < .05). The levels of collected CD34+ cells in light smoking were also obviously lower than that in nonsmoking donors ( P  < .05).There were no obvious differences in the collected CD34+ cells concentration, overall processed blood volume and total collected CD34+ cells between nonsmoking and smoking cessation groups ( P = .490; P = .464; P = .819). Conclusion: Cigarette smoking is an important factor that affects the yield of PBPCs in male donors, especially when the smoking load is more than five pack‐years. Mobilization of PBMCs could be restored by smoking cessation in chronic smokers.